Photovoltaic performance of heteroatom-doped boron nitride quantum dots in quantum dot photovoltaic cells - Peng Cui; Jian Zhang (Catalysis Communications, 2023)
The photovoltaic performance of C/O/S-doped hexagonal boron nitride (h-BN) quantum dots (QDs) is studied using density functional theory. Doping leads to occupied or unoccupied midgap states in h-BN QDs, resulting in a redshift in their absorption spectra. C-doping provides better charge transfer capability than S/O-doping. In addition, C-doping reduces the open-circuit voltage, light collection efficiency, fill factor, and driving forces of electron injection and reduction of h-BN QD. However, the fast non-radiative recombination deteriorates the energy conversion of C-doped h-BN QDs. The current study provides evidence for the rational design of photocatalytic devices based on h-BN QDs.